Nutrition of draught oxen in semi-arid West Africa. 1. Energy expenditure by oxen working on soils of different consistencies - Fall, Abdou; Pearson, R.A.; Lawrence, P.R. (Cambridge University Press, 1997)
The Oxylog, a portable breath-by-breath gas analyser, was used on seven animals to determine standing metabolic rate, energy cost of walking on soils of different consistencies and efficiency of work ploughing and carting. The average standing metabolic rate of animals was 5.63 (s.e. 0.12) W/kg M 0.75. The consistency of the soil on which animals worked had a marked effect on their energy cost of walking which was 1.59 (s.e. 0.069) on unploughed soil, 2.15 (s.e. 0.084) on ploughed soil and 1.0 (s.e. 0.10) j/m per kg live weight on laterite tracks. The efficiency of ploughing sandy soils (i.e. ratio of work done to energy used for work) was 0.32 and was not significantly different from the efficiency of carting with different loads. The efficiency of doing work was not influenced by the type of work performed, the draught force exerted or the walking speed.